MRI features of canine hemangiosarcoma affecting the central nervous system. Issue 2 (6th December 2021) - Mallol, Claudia; Gutierrez‐Quintana, Rodrigo; Hammond, Gawain; Schweizer‐Gorgas, Daniela; De Decker, Steven; Novellas, Rosa; Espada, Yvonne; Oevermann, Anna; Ortega, Maria; Parry, Andrew; Coelho, Ana Maria; Gonçalves, Rita; et al.
Abstract: Hemangiosarcoma is the most common metastatic tumor involving the brain in dogs but detailed published descriptions of the magnetic resonance imaging (MRI) features are lacking. The objective of this multi‐center, retrospective case series study was to describe MRI characteristics of canine hemangiosarcoma affecting the central nervous system (CNS). Medical records of seven referral institutions were retrospectively reviewed. Dogs were included if they had a histopathologically confirmed diagnosis of hemangiosarcoma affecting the CNS and undergone an MRI of the brain and/or vertebral column. Lesions were independently evaluated by two observers. Twenty dogs met the inclusion criteria and one dog had both intracranial and intramedullary hemangiosarcoma. Consistent MRI features included heterogeneous (17/21) lesions in all sequences with mainly mixed signal intensity (12/21), presence of susceptibility artifact on T2*w (15/16), associated moderate to severe perilesional edema (21/21), and moderate to strong (20/21) heterogeneous (14/21) or ring‐like (6/21) contrast enhancement. Intracranial hemangiosarcoma was frequently multiple and intra‐axial, affecting consistently the telencephalon and no differences in MRI features were found between primary and metastatic hemangiosarcoma. This is the first MRI description of primary intracranial hemangiosarcoma and primary intracranial epithelioid hemangiosarcoma. Vertebral hemangiosarcomas were segmental poorly marginated polyostotic and highly aggressive lesions invading the thoracic vertebral canal and paraspinal tissues. Epidural hemangiosarcomas were single and well‐marginated lesions in the thoracolumbar and/or lumbar region. Intramedullary hemangiosarcomas were cervical, metastatic in origin, and frequently (3/4) accompanied by intracranial lesions. These described MRI features will aid early identification of hemangiosarcoma guiding subsequent diagnostics and therapeutics.